Facile single-step technique for simultaneous in situ fabrication of Ag/Ag2S-polymer nanocomposites via PPS cyclization route - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Seth, Tanay; Amalnerkar, Dinesh P. (Chemistry Letters, 2008)
We herein propose a facile single-step approach involving solid-state reaction between silver salt and engineering thermoplastic polyphenylene sulfide for simultaneous in situ generation of nanoscale metallic silver as well as semiconducting silver sulfide.

Concurrent In-situ formation of Ag/Ag2S nanoparticles in polymer matrix by facile polymer-inorganic solid state reaction - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Hawaldar, Ranjit R.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Journal of Nano Research, 2009)
We herein report the feasibility of polymer-inorganic solid-state reaction route for simultaneous in situ generation of Ag & Ag2S nanostructures in polymer network wherein an engineering thermoplastic, polyphenylene sulphide (PPS), itself acts as a chalcogen source as well as a stabilizing matrix for the resultant nanoproducts. Typical solid-state reaction was accomplished by simply heating the physical admixture of the two reactants i.e. AgNO3 and PPS by varying molar ratios mainly 1:1, 1:5, 1:15, 1:20, at the crystalline melting temperature (285 degrees C) of PPS. The synthesized nanoparticles were characterized by various physico-chemical techniques like X-ray Diffractometry, Scanning Electron Microscopy equipped with EDAX, Transmission Electron Microscopy and UV-Visible spectroscopy. The prima facie observations suggest the effective formation and subsequent entrapment of mainly nanocrystalline metallic silver (fcc) in PPS matrix for all the molar ratios chosen for the reaction. Additionally, simultaneous occurrence of nanocrystalline Ag2S (monoclinic phase) is also noticed in case of heated admixture of AgNO3: PPS with equimolar ratio. The TEM analysis reveals nanoscale polydispersity (5nm to 70nm) and prevalence of mainly spherical morphological features in all the cases with occasional indications of triangular and hexagonal morphological features depending upon the reaction molar ratio.
Keywords: Ag; Ag2S; Nanoparticles; Polymer inorganic solid -state reaction; Thermoplastic polymer matrix

Tuning magnetic behavior of nanoscale cobalt sulfide and its nanocomposite with an engineering thermoplastic - Rumale, Narendra; Arbuj, Sudhir S.; Umarji, Govind; Shinde, Manish; Mulik, Uttam P.; Joy, Pattayil Alias; Amalnerkar, Dinesh P. (Journal of Electronic Materials, 2015)
Nanocomposites containing magnetic nanoparticles embedded in a polymer matrix with good thermal stability (up to 200A degrees C) are technologically important. We report an environmentally benign solid-solid approach for synthesis of cobalt sulfide and its nanocomposite using a thermally stable matrix of polyphenylene sulfide. Physicochemical characterizations reveal the formation of nanoclusters of the hexagonal phase CoS. Even though bulk CoS is nonmagnetic, magnetization studies exhibit anomalous magnetic behavior for phase-pure nanoscale CoS and its nanocomposites.
Keywords: Nanocomposite; polyphenylene sulfide; Solid-solid reaction; superparamagnetic

Concurrent synthesis of SnO/SnO2 nanocomposites and their enhanced photocatalytic activity - Roy, Animesh; Arbuj, Sudhir; Waghadkar, Yogesh; Shinde, Manish; Umarji, Govind; Rane, Sunit; Patil, Kashinath; Gosavi, Suresh; Chauhan, Ratna (Journal of Solid State Electrochemistry, 2017)
The SnO/SnO2 nanocomposites were synthesized using semisolvothermal reaction technique. These nanocomposites were prepared using different combination of solvents viz., ethanol, water, and ethylene glycol at 180 A degrees C for 24 h. The synthesized nanocomposites were analyzed with various characterization techniques. Structural analysis indicates the formation of tetragonal phase of SnO2 for the sample prepared in ethanol, whereas for other solvent combinations, the mixture of SnO and SnO2 having tetragonal crystal structures were observed. The optical study shows enhanced absorbance in the visible region for all the prepared SnO/SnO2 nanocomposites. The observed band gap was found to be in the range of 3.0 to 3.25 eV. Microstructural determinations confirm the formation of nanostructures having spherical as well as rod-like morphology. The size of nanoparticles in ethanol-mediated solvent was found to be in the range of 5 to 7 nm. Thermogravimetric analysis indicate the weight gain around 1.3 wt% confirming the conversion of SnO to SnO2 material. The photocatalytic activity of synthesized nanocomposites was evaluated by following the aqueous methylene blue (MB) degradation. The sample prepared in ethylene glycol-mediated solvent showed highest photoactivity having apparent rate constant (K-app) 0.62 x 10(-2) min(-1).
Keywords: Dye-degradation; Nanocomposite; Photocatalysis; tin oxide